2022
DOI: 10.1093/rheumatology/keac540
|View full text |Cite
|
Sign up to set email alerts
|

Association of mycophenolate and azathioprine use with cognitive function in systemic lupus

Abstract: Objectives Cognitive dysfunction (CD) is a common manifestation of systemic lupus erythematosus (SLE) which can have detrimental consequences for those affected. To date, no treatments have been approved for SLE- CD. This study aims to assess the association of azathioprine (AZA) and mycophenolate (MMF) use with SLE-CD, given that these medications have demonstrated neuroprotective qualities in prior studies. Methods Consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
3
2
0
Order By: Relevance
“…Compared with the other groups a higher absolute proportion of SLE patients with CI had musculoskeletal, renal, and muco-cutaneous involvement; however, this did not achieve statistical significance (Chi-square p=0.138, p=0.29, and p=0.134, respectively). The frequency of hypocomplementemia, anti-dsDNA, and APLA did not differ among the groups, and the medications that patients were taking were mostly similar, the only exception being significantly higher use of azathioprine (AZA) in non-CI patients (Chi-square p=0.001), which is consistent with our previous study ( 34 ).…”
Section: Resultssupporting
confidence: 90%
“…Compared with the other groups a higher absolute proportion of SLE patients with CI had musculoskeletal, renal, and muco-cutaneous involvement; however, this did not achieve statistical significance (Chi-square p=0.138, p=0.29, and p=0.134, respectively). The frequency of hypocomplementemia, anti-dsDNA, and APLA did not differ among the groups, and the medications that patients were taking were mostly similar, the only exception being significantly higher use of azathioprine (AZA) in non-CI patients (Chi-square p=0.001), which is consistent with our previous study ( 34 ).…”
Section: Resultssupporting
confidence: 90%
“…In support of our previous study, 29 we again found azathioprine use to be associated with CD in SLE. This is not surprising as the same cohort was used in both analyses.…”
Section: Discussionsupporting
confidence: 92%
“…5 This is discussed in more detail in our previous paper. 29 In summary, the contrast between our study findings and the existing literature from animal models reinforces the notion that CD in SLE is a multifactorial and complex process. 5 11 19 21 57-59 Despite our negative findings, the mounting body of mechanistic evidence supporting the role of cACEi/cARB in patients with CD suggests that further human studies are warranted to investigate cACEi/cARB as a potential treatment for SLE-CD, and in particular randomised controlled trials.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, immunomodulators are also receiving attention for their potential in the prevention and treatment of cognitive dysfunction. For example, some studies have found that the use of immunosuppressants like cyclosporine A and azathioprine can alleviate cognitive dysfunction ( Dobrowolski et al, 2023 ; Tapia-Monsalves et al, 2023 ).…”
Section: Some Preventive Strategies For the Peripheral Inflammation P...mentioning
confidence: 99%